SYED MUHAMMAD NAQUIB AL-ATTAS AND THE DIALOGIC OF OCCIDENTAL KNOWLEDGE: A Passing Glance to the Study of Society in the Malay Archipelago - Ahmad Murad Merican, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2021)
Syed Muhammad Naquib al-Attas’ writings have developed a framework and theoretical perspective in responding to the Western worldview and scholarship. This is another layer in the trajectory of his works which has mainly gone unnoticed from the beginning. His systematic corpus on the Anglo-Saxon West encompasses, among others, the philosophical and the metaphysical, axiological, moral-cultural, aesthetics and the linguistic dimensions. The dynamics is more often seen in light of Islamic philosophy and metaphysics, as well as Malay-Muslim attitudes and worldview. Al-Attas’ arguments are strongly critical of Western epistemology, European history and society. This essay revisits and rereads two of his works, namely Islam and Secularism, and a journal article, “Islamic Philosophy: An Introduction.” In both works, al-Attas resonates the image of the West in challenging its scholarship.